From Academia to entrepreneur : Lessons from the real world. - Khor, Eugene (Academic Press, 2013)
This book provides insights into using academic research as a potential business, meeting the challenges and opportunities in today's academic research environment.
1. Entrepreneuring academic biomedical science -- 2. The academic-business conundrum -- 3. Taking academic biomedical research beyond the lab bench -- 4. To become a runway entrepreneur from academia -- 5. What is the business? -- 6. Business plan -- 7. Raising funds -- 8. About meeting regulatory requirements -- 9. About consultants -- 10. Action plan -- 11. When the rubber hits the road -- 12. A few additional lessons from the battle front -- 13. Arrival.
Print version record.
Includes bibliographical references and index.
Text in English.
Keywords: Entrepreneurship; Entrepreneuriat; entrepreneurs; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Entrepreneurship